2004
DOI: 10.1086/422681
|View full text |Cite
|
Sign up to set email alerts
|

Warm Molecular Gas in Galaxy-Galaxy Merger NGC 6090

Abstract: We present Submillimeter Array observations of the CO (2-1) and (3-2) transitions toward the merging galaxies of NGC 6090. The high-resolution CO data reveal three gas concentrations. The main component is peaking in the overlap region between the two galaxies, where the near-IR and radio continuum emission are weak. The CO (2-1) emission from the face-on galaxy NGC 6090E is somewhat stronger than that from the edge-on galaxy NGC 6090W. The CO (3-2) emission peaks in the overlap region, similar to the CO (2-1)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The latter is a more realistic result, given the supporting evidence from Papers I and II and direct observations (e.g., Sanders et al 1988;Dupraz et al 1990;Wang et al 1991Wang et al , 1992Wang et al , 2004Casoli et al 1991;Hibbard et al 1994;Yun & Hibbard 2001).…”
Section: Summary and Discussionmentioning
confidence: 73%
“…The latter is a more realistic result, given the supporting evidence from Papers I and II and direct observations (e.g., Sanders et al 1988;Dupraz et al 1990;Wang et al 1991Wang et al , 1992Wang et al , 2004Casoli et al 1991;Hibbard et al 1994;Yun & Hibbard 2001).…”
Section: Summary and Discussionmentioning
confidence: 73%
“…Rigopoulou et al (1996) reported a CO J ¼ 2 1 survey of six ULIRGs, and Yao et al (2003) presented the first survey of CO J ¼ 3 2 emission of LIRGs and ULIRGs from the Scuba Local Universe Galaxy Survey (SLUGS). Recent high-resolution studies of warm, dense molecular gas in individual LIRGs have been performed by Iono et al (2004) and Wang et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Such a geometry has first been suggested by Kneib et al based on the UV/optical morphology of the potential two nuclei (their regions α and β) and the reddened overlap region (their region γ). Such active overlap regions are often found in nearby interacting systems (e.g., the Antennae: Wilson et al 2000;NGC 6090: Bryant & Scoville 1999;Wang et al 2004).…”
Section: Discussionmentioning
confidence: 98%